Performance of Segmental Post-Τensioned Concrete Beams Exposed to High Fire Temperature - Hekmet, H. M.; Izzet, A. F. (Engineering, Technology & Applied Science Research, 2019)
The present study illustrates observations, record accurate description and discussion about the behavior of twelve tested, simply supported, precast, prestressed, segmental, concrete beams with different segment numbers exposed to high fire temperatures of 300°C, 500°C, and 700°C. The test program included thermal tests by using a furnace manufactured for this purpose to expose to high burning temperature (fire flame) nine beams which were loaded with sustaining dead load throughout the burning process. The beams were divided into three groups depending on the precast segments number. All had an identical total length of 3150mm but each had different segment number (9, 7, and 5 segments), in other words, different segment lengths. To simulate genuine fire disasters, the nine beams were exposed to high-temperature flames for one hour along with the control specimens. The selected temperatures were 300°C (572°F), 500°C (932°F), and 700°C (1292°F) as recommended by the standard fire curve (ASTM–E119). The specimens were cooled gradually at ambient laboratory conditions. The performance of the prestressed segmental concrete beams through the burning process was described with regard to the beams camber, spalling, and occurred deterioration.